2021
DOI: 10.1111/andr.12976
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of pre‐operative blood parameters in forecasting varicocelectomy success?

Abstract: Background We aimed to examine the effects of pre‐operative blood values on varicocelectomy success. Materials and methods A total of 130 patients who underwent varicocelectomy in our clinic were retrospectively analyzed. Operation success was defined as the return of all semen parameters (concentration, progressive motility, and morphology) to normal values 6 months after surgery. The patients were separated as two groups as benefiting from the treatment (Group A) and not (Group B). Results The best cut‐off v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In another study, Erdoğan et al reported that the group whose semen parameters improved after varicocelectomy included patients with low NLR and high MPV. They determined the cutoff value as 2.27 for NLR (Erdogan et al, 2021). Similarly, in this study, NLR and MLR were found to be significant parameters in predicting the success of varicocelectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Erdoğan et al reported that the group whose semen parameters improved after varicocelectomy included patients with low NLR and high MPV. They determined the cutoff value as 2.27 for NLR (Erdogan et al, 2021). Similarly, in this study, NLR and MLR were found to be significant parameters in predicting the success of varicocelectomy.…”
Section: Discussionmentioning
confidence: 99%
“…9 In previous studies in patients with varicocele, neutrophil-lymphocyte ratio (NLR), lymphocyte-monocyte ratio (LMR) and platelet-lymphocyte ratio (PLR) were used to predict prognosis. 10 In addition, the systemic immune inflammation index (SII) and systemic inflammation response index (SIRI) in inflammatory diseases and various cancers have been studied as more complex inflammatory markers. 11,12 Since 2014, a new index called the SII (neutrophil × platelet/lymphocyte) has been used.…”
Section: Introductionmentioning
confidence: 99%